Distributional implications of climate change in India - Jacoby, Hanan (The World Bank, 2011)
Global warming is expected to heavily impact agriculture, the dominant source of livelihood for the world's poor. Yet, little is known about the distributional implications of climate change at the sub-national level. Using a simple comparative statics framework, this paper analyzes how changes in the prices of land, labor, and food induced by modest temperature increases over the next three decades will affect household-level welfare in India. The authors predict a substantial fall in agricultural productivity, even allowing for farmer adaptation. Yet, this decline will not translate into a sharp drop in consumption for the majority of rural households, who derive their income largely from wage employment. Overall, the welfare costs of climate change fall disproportionately on the poor. This is true in urban as well as in rural areas, but, in the latter sector only after accounting for the effects of rising world cereal prices. Adaptation appears to primarily benefit the non-poor, since they own the lion's share of agricultural land. The results suggest that poverty in India will be roughly 3-4 percentage points higher after thirty years of rising temperatures than it would have been had this warming not occurred